To excise or not: impact of MelaFind on German dermatologists' decisions to biopsy atypical lesions. (18th June 2014) - Hauschild, Axel; Chen, Suephy C.; Weichenthal, Michael; Blum, Andreas; King, Hadley C.; Goldsmith, Jeff; Scharfstein, Daniel; Gutkowicz‐Krusin, Dina
Summary Objectives To determine the biopsy sensitivity to melanoma of dermatologists in Germany and the impact of MelaFind® on their decisions to biopsy melanomas. Design Randomized two‐armed online reader study presenting case information, clinical/dermatoscopic images of pigmented skin lesions and MelaFind results (Arm 2). Methods Each participant was asked to review 130 pigmented skin lesions. Biopsy decisions of dermatologists without MelaFind versus MelaFind and dermatologists without MelaFind versus dermatologists with MelaFind were compared. Results Dermatologists without MelaFind had average sensitivity to melanoma of 69.5 % and average specificity of 55.9 %. MelaFind had greater sensitivity than dermatologists alone (96.9 % vs. 69.5 %, one‐sided p < 0.00001) and lower specificity (9.2 % vs. 55.9 %, one‐sided p < 0.00001). Dermatologists with MelaFind had higher sensitivity than those without MelaFind (78 % vs. 69.5 %, one‐sided p < 0.00001) and a lower specificity (45.8 % vs. 55.9 %, one‐sided p < 0.00001). The number of dermatologists detecting over 90 % of melanomas increased from 3 of 101 without MelaFind to 22 of 101 with MelaFind (p = 0.00006) while specificity remained relatively equivalent (23 % vs. 21 %, p = 0.99). Conclusions The MelaFind information, when incorporated into the final biopsy decision, can improve biopsy sensitivity with modest effect on biopsy specificity.